IMPROVEMENT OF PRODUCT QUALITY IN LADDER INDUSTRY ENTERPRISES ON THE BASIS OF STANDARDIZED QUALITY MANAGEMENT SYSTEM REQUIREMENTS - Kakhramonov Mukhammadali Abdullajan ugli; Kasimov Akhtamhon Akramovych (Scholars Digest Publishing, 2024)
This article investigates the topic of how sawmilling sector businesses' operations are affected by the implementation of а standardized quality management system. The writers conducted scientific research in 2024 to enhance the procedures and quality of goods produced at the Republic of Uzbekistan's currently operating sawmilling firms. Determining the effect of the requirements of the standardized quality management system on the operations of sawmilling sector firms is the primary goal and concern of the research conducted. Our ability to analyze the study questions and determine the following is made possible by the scientific research procedure and the analysis of the data collected: the primary prerequisites for the implementation of standardized quality management system requirements for the production process, statistical analysis of export data, and internal and external factors that aid in improving product quality are for sawmilling industry enterprises to adopt QMSs. The enhancement of foundational procedures and frameworks at sawmilling industry businesses is greatly influenced by standardized quality management systems.
Keywords: SMT, quality, management, enterprise, industry, system, process, improvement, product, improvement, statistical analysis.